Excess Sensitivity and Financial Development in the Iranian Households - Amineh Mahmoudzadeh; Kamyab Rajabizadeh; Majid Einian (پژوهشهای اقتصادی)
Aim and introduction The conventional notion of the permanent income hypothesis is that individuals aim to smooth their consumption over time, demonstrating resistance to fluctuations in income. This foundational concept assumes that individuals utilize savings or credit when faced with expected income changes or temporary income shocks, preserving their ultimate well-being. However, empirical evidence challenges this hypothesis, revealing that consumers often exhibit responsiveness to income changes, both expected and temporary. This phenomenon is called "excess sensitivity of consumption". Various factors underpin this apparent excess sensitivity of consumption, encompassing demographic dynamics, labor market decisions, reliance on aggregated data, superior information within households, income measurement inaccuracies, and liquidity constraints. Methodology This study employs the Panel-IV method to estimate the coefficient of excess sensitivity of consumption. It utilizes two financial development indicators, namely access to financial services and financial depth, to evaluate their impact on this coefficient. The significance of this investigation lies in the Iranian economic history, which witnessed financial development in the late 1990s, followed by a financial downturn. The data are derived from household income and expenditure surveys conducted by the Iranian Statistical Center. The analysis encompasses the years 2004 to 2020. These surveys incorporate data on various aspects of household’s financial information, including the amount and number of loans received and essential details about their employment status. Due to the cross-sectional nature of the data, it is imperative to use a pseudo-panel approach, providing several advantages. First, it eliminates the individual-specific measurement errors. Second, it mitigates the issues arising from the short time series data, which can lead to estimation errors. Previous research has estimated the coefficient of excess sensitivity of consumption. However, this study contributes by examining the effects of financial development on consumption smoothing in the Iranian economy. Notably, previous research in Iran focused solely on estimating the coefficient of excess sensitivity of consumption without investigating the influence of financial development. Findings The findings indicate the excess sensitivity of consumption coefficient is 0.266 for the Iranian households. In practical terms, a 10% expected increase in income results in a 2.66% increase in consumption. This finding indicates liquidity constraints faced by the Iranian households. Such constraints may manifest as limitations on borrowing amounts or high interest rates, leading individuals to opt for non-borrowing. The examination of financial development reveals a negative and significant relationship between improved financial access and depth and the coefficient of excess sensitivity of consumption. Specifically, a 10% improvement in the average loan amount and loan-to-income ratio (financial depth indicators) results in 12.5% and 13% reductions, respectively, in the coefficient of excess sensitivity of consumption. Additionally, a 10% enhancement in the average number of loans received by households (financial access indicator) leads to an impressive 20.5% reduction in the coefficient of excess sensitivity of consumption. Discussion and Conclusion This study challenges the traditional concept of permanent income hypothesis while emphasizing the importance of understanding excess sensitivity of consumption in economic research. Furthermore, it underscores the role of financial development, characterized by improved access to credit and financial services, in diminishing households' vulnerability to income fluctuations. These results hold substantial implications for policymakers and researchers alike, offering insights into addressing income volatility and its effects on household consumption in Iran and similar economies